A new fish species of Roeboides from Panamá (Characiformes: Characidae) - Alberto S. de Lucena, Carlos (2011)
A freshwater fish Roeboides loftini n.sp. is described from the Río Coclé del Norte drainage of the Atlantic versant of Panamá. The new species differs from other species of the Roeboides guatemalensis-group by the number of perforated scales on the lateral line (83-100), body depth (31.8-36.1%), predorsal distance (49.1-51.9%) and the shape of the humeral spot.